Cultural Competence and the Higher Education Sector Australian Perspectives, Policies and Practice - Frawley, Jack; Russell, Gabrielle; Sherwood, Juanita (Springer Nature Singapore : Imprint: Springer, 2020)
This open access book explores cultural competence in the higher education sector from multi-disciplinary and inter-disciplinary perspectives. It addresses cultural competence in terms of leadership and the role of the higher education sector in cultural competence policy and practice. Drawing on lessons learned, current research and emerging evidence, the book examines various innovative approaches and strategies that incorporate Indigenous knowledge and practices into the development and implementation of cultural competence, and considers the most effective approaches for supporting cultural competence in the higher education sector. This book will appeal to researchers, scholars, policy-makers, practitioners and general readers interested in cultural competence policy and practice.